The Repertoire Policy in The Period of Repressions in Soviet Armenia (1936-1954) - Shamamyan, Narine (History and Culture, 2025)
In the early period of Soviet Armenia, the relations between politicians and culture were closely related. Without the permission of the Center for Culture Agitation, which was under strict local and Moscow control, the repertoire of any cultural sphere was not compiled. Poems and songs dedicated to Lenin-Stalin, as well as Beria were considered compulsively in the program, and the communist symbols - hammer and sickle, the star was mainly expressed in dance performances. During the period of the Cult of Personality (1920-1954), the task was to create an international, socialist culture. The standard of evaluation of the artistic work was considered to be "National in form, socialist in content". Our task to discuss dance culture during the period of Stalinist Repressions, in particular to reflect on the banning of folk dances and the programmatic politics of creating new contemporary dance performances. Culture, particularly dance, took on an ideological tone. The figures of Stalin, Lenin, Beria have been considered political symbols were included in the dance performances. Before the started the concert as a rule had been performed the international song of the “Nations of the Soviet Union”, then pronounced and were played of poems, songs with political content, which have been dedicated to Stalin, Lenin and Beria. During that period, Srbuhi Lisitsyan staged agit-performances: “Cominter”, “Struggle against cracks”, “Wounded flag bearer”, “Hammer and sickle”, “German police and communist”, “Viva red China”, as well as “Pioneer” ballet, among the performances of Tatul Altunyan’s “Song-dance” ensemble is “Soldier’s Dance”, “Dance of Sevan fishermen” and others. It should be noted that in connection with the establishment of the Soviet Union in 1938 the festival of “literature and Art” was organized in Moscow, in which Armenia also participated. Armenia was represented by Tatul Altunyan’s “Song-dance” ensemble, Srbuhi Lisitsyan’s “Rhythm and Plastic” Studio, and ‘’Sasun’’ dance group from Ashnak village led by Vahram Aristakesyan. The Sasun’s folk dance presenting in the stage was an extremely bold move during the active period of Stalinist repression, which did not remain without consequences. In the same year, Vahram Aristakesyan was accused of espionage and the great figure of the dance art was arrested. In the Soviet period, reference to traditional culture was prohibited and negatively assessed, it was impossible to create homeland-diaspora ties, and those who tried to create them were condemned with heavy charges.